Drug-induced kidney stones: a real-world pharmacovigilance study using the FDA adverse event reporting system database - Ding, Pan; Luo, Qinghua; Cao, Leihua (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to identify the drugs most commonly associated with kidney stone-related adverse events using data from the FDA Adverse Event Reporting System (FAERS), providing insights for clinical reference regarding the use of these drugs.MethodsWe utilized the Medical Dictionary for Regulatory Activities (MedDRA 26.0) preferred term “nephrolithiasis” to identify drug-related adverse events (ADEs) for kidney stones reported in FAERS from Q1 2004 to Q1 2024. Reporting odds ratio (ROR) was used to quantify the signal strength of these ADEs, and new risk signals for kidney stones were compared with drug labeling information to identify any previously unreported risks.ResultsOut of 21,035,995 adverse events reported in FAERS, 38,307 were associated with kidney stones. The top 5 drugs most frequently linked to kidney stone cases were adalimumab (2,636 cases), infliximab (1,266 cases), interferon beta-1a (920 cases), sodium oxybate (877 cases), and teriparatide (836 cases). Notably, certain drugs like lansoprazole (ROR 7.2, 95% CI 6.62–7.84), Xywav (ROR 7.1, 95% CI 6.03–8.35), and teduglutide (ROR 5.54, 95% CI 4.83–6.36) showed significant risk signals. Of the 50 drugs identified, 33 were not previously labeled as carrying a risk of kidney stones.ConclusionOur analysis of FAERS data revealed new risk signals for kidney stones not indicated in the labels of 33 drugs. Close monitoring is recommended when using these medications, and further research is needed to investigate the mechanisms behind drug-induced kidney stone formation.